Digital interventions to promote self-management in adults with hypertension systematic review and meta-analysis. Issue 4 (April 2016) - McLean, Gary; Band, Rebecca; Saunderson, Kathryn; Hanlon, Peter; Murray, Elizabeth; Little, Paul; McManus, Richard J.; Yardley, Lucy; Mair, Frances S.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To synthesize the evidence for using interactive digital interventions (IDIs) to support patient self-management of hypertension, and to determine their impact on control and reduction of blood pressure. Method: Systematic review with meta-analysis was undertaken with a search performed in MEDLINE, EMBASE, CINAHL, PsycINFO, ERIC, Cochrane Library, DoPHER, TROPHI, Social Science Citation Index and Science Citation Index. The population was adults (>18 years) with hypertension, intervention was an IDI and the comparator was usual care. Primary outcomes were change in SBP and DBP. Only randomized controlled trials and studies published in journals and in English were eligible. Eligible IDIs included interventions accessed through a computer, smartphone or other hand-held device. Results: Four out of seven studies showed a significantly greater reduction for intervention compared to usual care for SBP, with no difference found for three. Overall, IDIs significantly reduced SBP, with the weighted mean difference being −3.74 mmHg [95% confidence interval (CI) −2.19 to −2.58] with no heterogeneity observed (I-squared = 0.0%, P  = 0.990). For DBP, four out of six studies indicated a greater reduction for intervention compared to controls, with no difference found for two. For DBP, a significant reduction of −2.37 mmHg (95% CI −0.40 to −4.35) was found, but considerable heterogeneity was noted (I-squared = 80.1%, P  = <0.001). Conclusion: IDIs lower both SBP and DBP compared to usual care. Results suggest these findings can be applied to a wide range of healthcare systems and populations. However, sustainability and long-term clinical effectiveness of these interventions remain uncertain.